1995
DOI: 10.2166/wst.1995.0523
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium removal during water treatment using dissolved air flotation

Abstract: The occurrence of the protozoan parasite Cryptosporidium parvum in water supplies, and the resultant outbreaks of cryptosporidiosis in the UK and USA, have led to concern over the ability of conventional water treatment processes to remove Cryptosporidia from water sources. Large scale pilot plant trials of water treatment have been carried out in the UK to establish the degree of removal that can be achieved by a range of treatment processes, including dissolved air flotation, and to compare the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…Several pilot-and fullscale studies have demonstrated that organism-sized particles and turbidity are approximate indicators of pathogen removal by drinking water treatment processes but are not reliable quantitative surrogates (Huck et al, 2002(Huck et al, , 2001Emelko, 2001;Nieminski & Ongerth, 1995;LeChevallier & Norton, 1992). In some cases, increased Cryptosporidium passage through filters has been associated with increased filtrate turbidity (Hall et al, 1995;Nieminski & Ongerth, 1995). However, when parameters such as turbidity and particle counts are assessed as surrogates for Cryptosporidium removal by filters, it is important that the surrogates be applicable to the range of conditions encountered during typical operation.…”
Section: Particle Surrogate and Cryptosporidium Removal By Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pilot-and fullscale studies have demonstrated that organism-sized particles and turbidity are approximate indicators of pathogen removal by drinking water treatment processes but are not reliable quantitative surrogates (Huck et al, 2002(Huck et al, , 2001Emelko, 2001;Nieminski & Ongerth, 1995;LeChevallier & Norton, 1992). In some cases, increased Cryptosporidium passage through filters has been associated with increased filtrate turbidity (Hall et al, 1995;Nieminski & Ongerth, 1995). However, when parameters such as turbidity and particle counts are assessed as surrogates for Cryptosporidium removal by filters, it is important that the surrogates be applicable to the range of conditions encountered during typical operation.…”
Section: Particle Surrogate and Cryptosporidium Removal By Filtrationmentioning
confidence: 99%
“…Despite decreases in oocyst removals relative to stable operation, maintained Cryptosporidium removals of >3 logs during filter ripening have been reported (Swaim et al, 1996). Several pilot-scale studies have indicated that oocyst removals decrease by ~0.5-1 log during filter ripening (Huck et al, 2002(Huck et al, , 2001Emelko, 2001;Swaim et al, 1996;Hall et al, 1995;Patania et al, 1995). These findings were also demonstrated at full-scale by Baudin and Laîné (1998) who reported ~1-log deterioration in oocyst removals during filter ripening.…”
Section: (Low Alum Dose)mentioning
confidence: 99%
“…They found the combination of DAF and dual‐media filtration resulted in Cryptosporidium removals of 4–5 log. Hall et al 13 found DAF and filtration resulted in Cryptosporidium removals of 3–4 log.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation and DAF conditions that minimize residual turbidity and maximizes organic removal also produced high log removals of Cryptosporidium. Hall et at. (1995) reported on results from large scale pilot plant tests to determine the degree of Cryptosporidium removal that can be achieved by a variety of treatment processes including DAF.…”
Section: Sedimentationmentioning
confidence: 99%
“…Compared to the 30% of dichloroethane lost as air emissions from conventional bioreactors, less than 1.5% of the dichloroethane was lost as an air emission in the membrane bioreactors. Hall et at. (1995) investigated the feasibility of an anaerobic membrane bioreactor for treatment of segregated kraft bleach plant wastewaters and removal of adsorbable organic halogen (AOX).…”
Section: Membrane Processesmentioning
confidence: 99%